Toponymic Data Helps to Reveal the Occurrence of Previously Unknown Populations of Wild Zamia pumila L. on Volcanic Substrates in South Central Puerto Rico - Pagán-Jiménez, Jaime R.; Lazcano-Lara, Julio C. (Ethnobiology Letters, 2013)
This is the first report of the occurrence of wild Zamia pumila L. Zamiaceae populations on various volcanic substrates in the piedmont area of south central Puerto Rico. Data acquisition and its field confirmation were possible after the identification of toponymic names in old and current maps, and historic documents of the island in which one of the indigenous names for the genus (marunguey [marungüey] or marungueyes) has been used for naming some localities. These preliminary data have deep implications for paleo- and neoethnobotanical research, and for population ecology of the species in Puerto Rico, because they expand the traditionally accepted range for the species on the island. Zamia has been described as one of the main food plants among pre- and post-Columbian inhabitants in two islands of the Greater Antilles, Hispaniola and Puerto Rico, where the most sophisticated pre-Columbian society of the Antilles, the Taínos, emerged. Our findings suggest that Zamia might have been more available to humans, as a food source, than previously thought.